Inovasi dalam Pembelajaran Matematika: Meningkatkan Pemahaman Konsep Melalui Alat Peraga di SD - Juliana Sumilat Margareta; Fitriah Mochtar (Departement of Mathematics Education, 2024)
Innovation in mathematics learning at the Elementary School (SD) is discussed in this article, particularly how the use of teaching aids enhances conceptual understanding. Students can use teaching aids to understand abstract mathematical concepts in a more visual and concrete way. This study examines previous research on how teaching aids, such as math blocks, interactive whiteboards, and manipulatives, function to enhance students' understanding of mathematics in elementary school. These teaching aids have proven effective in improving students' comprehension of basic math concepts, such as addition, subtraction, multiplication, division, and geometry. The literature review indicates that structured use of teaching aids can increase student engagement, enhance conceptual understanding, and support more active and enjoyable learning. Therefore, the innovation of learning through teaching aids is highly recommended to be implemented in mathematics teaching practices in elementary schools to make the mathematics learning experience more effective and enjoyable for students.